2020
DOI: 10.1002/oby.23039
|View full text |Cite
|
Sign up to set email alerts
|

Sex Affects Regional Variations in Subcutaneous Adipose Tissue T Cells but not Macrophages in Adults with Obesity

Abstract: ObjectiveThe inflammatory environment in lower‐body subcutaneous adipose tissue (SAT) has been largely unexplored. This study aimed to examine the effects of region (upper body vs. lower body) and sex on SAT immune cell profiles in young adults with obesity.MethodsAbdominal (AB) and femoral (FEM) SAT was collected from 12 males (mean [SEM] age = 30.8 [1.4] years; mean [SEM] BMI = 34.1 [1.1] kg/m2) and 22 females (mean [SEM] age = 30.6 [0.6] years; mean [SEM] BMI = 34.0 [0.7] kg/m2) with obesity via needle aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
2
3
1
Order By: Relevance
“…In humans, few sex differences in macrophages have so far have been noted. This includes results from our own lab, which found no sex difference in the number of M2 like (CD68+ CD206+) and M1 like (CD68+ CD206−) macrophages per g abdominal or femoral SAT 76 . However, in both sexes, there were greater numbers of M1 like cells (CD68+ CD206−) per g in abdominal versus femoral SAT 76 .…”
Section: Immune Cellssupporting
confidence: 56%
See 4 more Smart Citations
“…In humans, few sex differences in macrophages have so far have been noted. This includes results from our own lab, which found no sex difference in the number of M2 like (CD68+ CD206+) and M1 like (CD68+ CD206−) macrophages per g abdominal or femoral SAT 76 . However, in both sexes, there were greater numbers of M1 like cells (CD68+ CD206−) per g in abdominal versus femoral SAT 76 .…”
Section: Immune Cellssupporting
confidence: 56%
“…In humans, the presence of proinflammatory cytotoxic T cells (CD8+) appears greater in the omentum than abdominal SAT in males and females 86 . However, with regard to SAT, we have observed that females have greater T helper (CD4+) and cytotoxic (CD8+) T‐cell subsets in femoral SAT compared with abdominal SAT, whereas in males no differences were found between the two depots 76 …”
Section: Immune Cellscontrasting
confidence: 50%
See 3 more Smart Citations